Truancy: The relevance of resilience internal assets, student engagement and perception of success, for youth living with parents and in residential care - Santos, A. C.; Simões, C.; Branquinho, C.; Arriaga, P. (Child Abuse and Neglect, 2023)
Background: School absenteeism is associated with multiple negative short and long-term impacts, such as school grade retention and mental health difficulties. Objective: The present study aimed to understand the role of resilience-related internal assets, student engagement, and perception of school success as protective factors for truancy. Additionally, we investigated whether there were differences in these variables between students living in residential care and students living with their parents. Method: This study included 118 participants aged 11 to 23 years old (M = 17.16, SE = 0.26). The majority were female (n = 61, 51.7 %) and Portuguese (n = 98, 83.1 %), with half living in residential care. In this cross-sectional study, participants responded to self-report questionnaires. Hierarchical regression analysis was used to understand the factors associated with truancy. Results: There were no group differences in resilience-related internal assets and their perception of school success. On the contrary, participants in residential care reported more unexcused school absences, more grade retentions, higher levels of depression, and lower levels of student engagement. Moreover, hierarchical linear regression controlling for key variables (i.e., living in residential care or with parents, school grade retention, and depression) showed that perception of school success and resilience-related internal assets significantly contributed to truancy. Conclusions: Results are discussed in the context of universal and selective interventions. These interventions can foster individual strengths and provide opportunities for every student to experience success. Consequently, they promote engagement and reduce the likelihood of school absences, especially for those in more vulnerable situations such as youth in residential care.